(untitled) (Praxis Educativa, 2025)
This article addresses the topic Social Movements and Education. It is oriented towards the study of social organizations that in local contexts develop alternative educational projects to the state proposal. We present here the experience of the Peasant Schools. These arise as a result of the demand for secondary schools in rural areas of the north and northwest of Córdoba. It was promoted by the Peasant Movement of Córdoba (MCC) before the Ministry of Education in 2008. Due to their conditions of origin, the schools are closely linked to objectives of political training and defense of the territory, which gives them unique characteristics. Our investigation focuses on the way in which the political program of the MCC is intertwined with the pedagogical proposal of the Schools, in which secondary programs are implemented for adults and young people from 14 to 17 years old.